PM2.5 induces the distant metastasis of lung adenocarcinoma via promoting the stem cell properties of cancer cells. (1st March 2022) - Pan, Junyi; Xue, Yueguang; Li, Shilin; Wang, Liuxiang; Mei, Jie; Ni, Dongqi; Jiang, Jipeng; Zhang, Meng; Yi, Shaoqiong; Zhang, Rong; Ma, Yongfu; Liu, Yang; et al.
Abstract: Lung cancer is the most common cancer in China and second worldwide, of which the incidence of lung adenocarcinoma is rising. As an independent factor, air pollution has drawn the attention of the public. An increasing body of studies has focused on the effect of PM2.5 on lung adenocarcinoma; however, the mechanism remains unclear. We collected the PM2.5 in two megacities, Beijing (BPM) and Shijiazhuang (SPM), located in the capital of China, and compared the different components and sources of PM2.5 in the two cities. Vehicle emissions are the primary sources of BPM, whereas SPM is industrial emissions. We found that chronic exposure to PM2.5 promotes the tumorigenesis and metastasis of lung adenocarcinoma in patient-derived xenograft (PDX) models, as well as the migration and invasion of lung adenocarcinoma cell lines. SPM has more severe effects in vivo and in vitro . The underlying mechanisms are related to the stem cell properties of cancer cells, the epithelial-mesenchymal transition (EMT) process, and the corresponding miRNAs. It is hopeful to provide a theoretical basis for improving air pollution in China, especially in the capital area, and is of the significance of long-term survival of lung cancer patients. Graphical abstract: Image 1 Highlights: PM2.5 promote the metastasis of lung adenocarcinoma PDX models. PM2.5 from Shijiazhuang (SPM) has more severe effect than Beijing (BPM). PM2.5 promote the expression of CSCs-related genes of lung adenocarcinoma cell. PM2.5 regulated miRNA of CSCs-related pathway of lung adenocarcinoma cells.